Clinical Gastrointestinal Endoscopy A Comprehensive Atlas - Chun, Hoon Jai; Yang, Suk-Kyun; Choi, Myung-Gyu (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Gastrointestinal endoscopy is the principal tool for the investigation and treatment of most diseases of the gastrointestinal tract. The Clinical Gastrointestinal Endoscopy offers a comprehensive overview of the role of gastrointestinal endoscopy in diagnosis. The atlas contains an abundance of high-quality images of a wide range of diseases of the upper and lower gastrointestinal tract, accompanied by precise clinical descriptions. Normal findings and variants are also documented. Furthermore, many images obtained by means of advanced image-enhanced endoscopy, capsule endoscopy, device-assisted enteroscopy, and endoscopic ultrasound are included. This book will be an ideal reference for both specialists and trainees in gastroenterology. It will provide the reader with an invaluable store of knowledge and with the clear guidance required in order to perform gastrointestinal endoscopy to best effect. .